Competency Crosswalk: A Multispecialty Review of the Accreditation Council for Graduate Medical Education Milestones Across Four Competency Domains. (July 2018) - Edgar, Laura; Roberts, Sydney; Yaghmour, Nicholas A.; Leep Hunderfund, Andrea; Hamstra, Stanley J.; Conforti, Lisa; Holmboe, Eric S.
Abstract : Purpose: To identify common and overlapping themes among the interpersonal and communication skills (ICS), practice-based learning and improvement (PBLI), professionalism (PROF), and systems-based practice (SBP) milestones of the transitional year and 26 specialties. Method: In May 2017, milestones were accessed from the Accreditation Council for Graduate Medical Education specialties website. A thematic analysis of the ICS, PBLI, PROF, and SBP milestones was performed to determine unique and common themes across these competencies and across specialties. Keywords from the common program requirements were initially applied as codes to the milestones. Codes were then grouped into common themes. Results: Twenty-two themes were identified: 15 (68%) were unique to a given competency (3 related to ICS, 4 related to PBLI, 5 related to PROF, and 3 related to SBP), and 7 (32%) appeared in the milestones of more than one core competency. Eleven themes (50%) were used by 20 or more specialties, and 6 themes (27%) by 10 or fewer specialties. No theme was present across all specialties. Conclusions: The ICS, PBLI, PROF, and SBP milestones contain multiple themes with areas of overlap among these four competencies and substantial variability across specialties. This variability may create differential expectations of residents across specialties, complicate faculty development, and make sharing assessment tools difficult. The thematic analysis provides important insights into how individual specialties interpret and operationalize the ICS, PBLI, PROF, and SBP competency domains and can inform future revisions of milestones to enable harmonization and shared understanding of these competencies across specialties where appropriate. Abstract : Supplemental Digital Content is available in the text.